Azithromycin in viral infections - Oliver, Madeleine E. (Rev Med Virol, 2020)
Azithromycin (AZM) is a synthetic macrolide antibiotic effective against a broad range of bacterial and mycobacterial infections. Due to an additional range of anti‐viral and anti‐inflammatory properties, it has been given to patients with the coronaviruses SARS‐CoV or MERS‐CoV. It is now being investigated as a potential candidate treatment for SARS‐CoV‐2 having been identified as a candidate therapeutic for this virus by both in vitro and in silico drug screens. To date there are no randomised trial data on its use in any novel coronavirus infection, although a large number of trials are currently in progress. In this review, we summarise data from in vitro, murine and human clinical studies on the anti‐viral and anti‐inflammatory properties of macrolides, particularly AZM. AZM reduces in vitro replication of several classes of viruses including rhinovirus, influenza A, Zika virus, Ebola, enteroviruses and coronaviruses, via several mechanisms. AZM enhances expression of anti‐viral pattern recognition receptors and induction of anti‐viral type I and III interferon responses. Of relevance to severe coronavirus‐19 disease (COVID‐19), which is characterised by an over‐exuberant innate inflammatory response, AZM also has anti‐inflammatory properties including suppression of IL‐1beta, IL‐2, TNF and GM‐CSF. AZM inhibits T cells by inhibiting calcineurin signalling, mammalian target of rapamycin activity and NFκB activation. AZM particularly targets granulocytes where it concentrates markedly in lysosomes, particularly affecting accumulation, adhesion, degranulation and apoptosis of neutrophils. Given its proven safety, affordability and global availability, tempered by significant concerns about antimicrobial stewardship, there is an urgent mandate to perform well‐designed and conducted randomised clinical trials.